Analysis of the degradation of amorphous silicon-based modules after 11 years of exposure by means of IEC60891:2021 procedure 3 - Piliougine, Michel; Sánchez-Friera, Paula; Petrone, Giovanni; Sánchez-Pacheco, Francisco José; Spagnuolo, Giovanni; Sidrach-de-Cardona-Ortin, Mariano (Wiley, 2022)
The degradation of two amorphous silicon-based photovoltaic (PV) modules, namely, of single junction amorphous silicon (a-Si) and of micromorph tandem (a-Si/μ-Si), after 11 years of exposure in the south of Spain is analyzed. Their I-V curves were measured outdoors to study the changes of the electrical parameters in the course of three different periods: during the initial days of exposure, during the first year, and in the subsequent 10-year period. The translation of the curves to an identical set of operating conditions, which enables a meaningful comparison, was done by the dif ferent correction procedures described in the standard IEC60891:2021, including the procedure 3, which does not require the knowledge of module parameters, whose values are typically not available. The annual power degradation rates over the entire 11-year period are 1.12% for the a-Si module, which is 3.02% for the first year, and 0.98% for the a-Si/μ-Si, which is 2.29% for the initial year
Keywords: Silicio; Aamorphous silicon; IEC60891; I-V curve correction; Microcrystalline silicon; Outdoor measurement; Photovoltaic degradation; Thin film